Culturing the Plastisphere: comparing methods to isolate culturable bacteria colonising microplastics - Stevenson, Emily M.; Buckling, Angus; Cole, Matthew; Lindeque, Penelope K.; Murray, Aimee K. (Frontiers in Microbiology, 2023)
Microplastics quickly become colonised by diverse microbial communities, known as the Plastisphere. There is growing concern that microplastics may support the enrichment and spread of pathogenic or antimicrobial resistant microorganisms, although research to support the unique role of microplastics in comparison to control particles remains inconclusive. Limitations to this research include the microbiological methods available for isolating adhered microbes. Culture-based methods provide some of the most established, accessible and cost-effective microbiological protocols, which could be extremely useful in helping to address some of the remaining key questions in Plastisphere research. Previous works have successfully cultured bacteria from plastics, but these have not yet been reviewed, nor compared in efficiency. In this study, we compared four common biofilm extraction methods (swabbing, sonication, vortexing, sonication followed by vortexing) to extract and culture a mixed community of bacteria from both microplastic (polyethylene, polypropylene and polystyrene) and control (wood and glass) particles. Biofilm extraction efficiency and viability of bacterial suspension was determined by comparing CFU/mL of four different groups of bacteria. This was verified against optical density and 16S rRNA qPCR. Overall, we found that all tested methods were able to remove biofilms, but to varying efficiencies. Sonicating particles with glass beads for 15 minutes, followed by vortexing for a further minute, generated the highest yield and therefore greatest removal efficiency of culturable, biofilm-forming bacteria.